A multi-method synthesis of studies evaluating wellness-informed approaches to counselor supervision. Issue 2 (3rd July 2018) - Lenz, A. Stephen; Blount, Ashley J.; Norris, Caroline A.
ABSTRACT: This multi-method synthesis evaluated the effectiveness, course of effect, and perceived salient features of wellness-informed approaches to supervision. Synthesis of findings from between-groups ( j = 3), single-case ( j = 2), and qualitative ( j = 4) studies indicated preliminary support for these approaches to supervisee development. Recommendations for supervisors and limitations of findings to counselor preparation programs are discussed.